Molecular Dynamics Simulation Study of Parallel Telomeric DNA Quadruplexes at Different Ionic Strengths: Evaluation of Water and Ion Models - Rebič, Matúš; Laaksonen, Aatto; Šponer, Jiří; Uličný, Jozef; Mocci, Francesca (The journal of physical chemistry. B, 2016)
Most molecular dynamics (MD) simulations of DNA quadruplexes have been performed under minimal salt conditions using the Åqvist potential parameters for the cation with the TIP3P water model. Recently, this combination of parameters has been reported to be problematic for the stability of quadruplex DNA, especially caused by the ion interactions inside or near the quadruplex channel. Here, we verify how the choice of ion parameters and water model can affect the quadruplex structural stability and the interactions with the ions outside the channel. We have performed a series of MD simulations of the human full-parallel telomeric quadruplex by neutralizing its negative charge with K(+) ions. Three combinations of different cation potential parameters and water models have been used: (a) Åqvist ion parameters, TIP3P water model; (b) Joung and Cheatham ion parameters, TIP3P water model; and (c) Joung and Cheatham ion parameters, TIP4Pew water model. For the combinations (b) and (c), the effect of the ionic strength has been evaluated by adding increasing amounts of KCl salt (50, 100, and 200 mM). Two independent simulations using the Åqvist parameters with the TIP3P model show that this combination is clearly less suited for the studied quadruplex with K(+) as counterions. In both simulations, one ion escapes from the channel, followed by significant deformation of the structure, leading to deviating conformation compared to that in the reference crystallographic data. For the other combinations of ion and water potentials, no tendency is observed for the channel ions to escape from the quadruplex channel. In addition, the internal mobility of the three loops, torsion angles, and counterion affinity have been investigated at varied salt concentrations. In summary, the selection of ion and water models is crucial as it can affect both the structure and dynamics as well as the interactions of the quadruplex with its counterions. The results obtained with the TIP4Pew model are found to be closest to the experimental data at all of the studied ion concentrations.
Keywords: osmolární koncentrace; Potassium Chloride; simulace molekulární dynamiky; G-kvadruplexy; kationty; Nucleic Acid Conformation; Cations; Telomere; Water; Humans; telomery; lidé; Molecular Dynamics Simulation; Osmolar Concentration; chlorid draselný; voda; G-Quadruplexes; konformace nukleové kyseliny